Qayam-e-pakistan ki suchi kahanieyan - Imran, maqsood (Ferozsons Pakistan, 2001)
Qayam-e-Pakistan Ki Suchi Kahaniyan narrates inspiring true stories of individuals and events that contributed to the creation and development of Pakistan.